Robust Abatement Policy with Uncertainty About Environmental Disasters - Niu, Yingjie; Zou, Zhentao (Environmental and Resource Economics, 2024)
We consider the robust responses to environmental disasters in stochastic growth economies. The representative agent has imprecise knowledge about environmental disasters and exhibits ambiguity aversion to the jump arrival intensity. In the equilibrium, the optimal abatement expenditure is increasing in the level of ambiguity aversion, which overturns the effect of model uncertainty on capital investment. Because of mitigating future damages, the incremental abatement may enhance long-run economic growth. In addition, welfare gains from abatement technology and the social cost of carbon become more substantial under ambiguous circumstances. Finally, we extend the baseline model by considering emission stock and find the main results still hold in this extension.
Keywords: Ambiguity Aversion; Environmental Disasters; Social Cost of Carbon; Economic Growth